Sleeping sickness and other parasitic tropical diseases : deadly diseases throughout history - Ramen, Fred. (New York : Rosen Publishing Group, 2002)
Examines the microscopic world of the parasites that cause sleeping sickness and explains the origin of tropical diseases and their history.
Includes index.
Keywords: Tropical medicine -- Juvenile literature; African trypanosomiasis -- Juvenile literature; Parasitic diseases -- Juvenile literature; African trypanosomiasis; Tropical medicine